HOTS-Based Teaching Module Design Planning in the Independent Curriculum - Rosmiati; Arif Mahya Fanny; Bahauddin Azmy; Rarasaning Satianingsih; Susi Hermin Rusminati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In facing the current dynamics of education, big challenges arise with the introduction of the Independent Curriculum in Indonesia. The focus on developing higher-order thinking skills (HOTS) creates a deep need for planning teaching modules that are innovative and in line with new curriculum principles. The workshop is structured into several sessions which include an introduction to the HOTS concept, development of teaching modules, technology integration, and direct practice in creating module prototypes. This process is designed to provide an in-depth understanding and skills needed for elementary school teachers to be able to design teaching modules that are by the principles of the Independent Curriculum. Through a step-by-step approach, this workshop becomes a bridge towards implementing quality and relevant learning at the basic education level.